Structural Synthesis and Isomorphism Identification of Multi-DOF AT Planetary Gear Trains - Xue Huanzhang (Jixie chuandong)
Due to the large scale of AT planetary gear trains (PGTs) schemes with 4-5 degrees of freedom, the optimization time is too long. In order to be qualified for large-scale AT structural schemes synthesis, a link synthesis and isomorphism identification method based on string encoding is proposed. The characters of the links are defined according to each link type of the PGT, and the AT structure is converted into a string. By analyzing the characteristics of the brake links and interconnection links in the planetary gear set string, and using the combination principle to design a reasonable string synthesis algorithm, the isomorphism identification of the PGTs and the AT structures are realized respectively. During the synthesis of the AT structures, the PGT strings and AT structure strings that do not satisfy the link constraints are eliminated separately. The correctness and efficiency of the method are verified by five examples.